Acceptability and effects on mental health of a music-based virtual reality intervention in geriatric outpatients: results from a pilot randomized controlled trial - Galery, Kevin; Djerroud, Katia; Chabot, Julia; Sekhon, Harmehr; Tannou, Thomas; Gros, Auriane; Beauchet, Olivier (Frontiers in Virtual Reality, 2025)
BackgroundAlthough the benefits of music on mental health are well established, few studies have investigated the impact of delivering it through virtual reality (VR) technologies. VR offers immersive experiences that can enhance mental health benefits in geriatric patients. However, accessibility to VR music-based interventions for geriatric outpatients remains uncertain. This study aimed to evaluate the acceptability and effects of a music-based VR intervention on emotion, wellbeing and mood in geriatric outpatients living in Montreal (Quebec, Canada).MethodsA single-center randomized controlled trial (RCT) with two parallel arms (i.e., control versus intervention) was conducted at the Montreal Geriatric University Institute (Quebec, Canada). A total of 41 outpatients from the geriatric and memory clinics were recruited and randomly assigned in the control group (n = 20; music listening via headphones) and in the intervention group (n = 21; VR-based music experience). The primary outcome was the acceptability of the intervention assessed using three complementary criteria: adoption defined as a retention rate ≥80%, satisfaction defined as willingness to reuse the intervention and perceived mental health benefits, and tolerance using the Simulator Sickness Questionnaire [SSQ] score (high tolerance defined by a score ≤9). Secondary outcomes were the effect on emotional state assessed with the Positive and Negative Affect Schedule (PANAS), on wellbeing assessed with the Warwick-Edinburgh Mental Wellbeing Scale (WEMWBS) and on mood states assessed with the Visual Analog Mood Scale (VAMS).ResultsHigh retention (95.2%), satisfaction (85.0%) and tolerance (95%) rates were observed in the intervention group. The PANAS positive score significantly improved in the VR group (β = 15.9, 95% CI [6.8, 25.1], p = 0.001). No significant intergroup differences were observed for wellbeing and mood.InterpretationThis study demonstrates that a music-based VR intervention was highly acceptable and led to a significant improvement in positive emotional state among older adults in geriatric outpatients.Clinical trial registrationNCT06296199; https://clinicaltrials.gov/study/NCT06296199.